Increased admissions for diabetes mellitus after burn. Issue 8 (December 2016) - Duke, Janine M.; Randall, Sean M.; Fear, Mark W.; Boyd, James H.; O'Halloran, Emily; Rea, Suzanne; Wood, Fiona M.
Highlights: Increased post-burn admissions for diabetes mellitus after burns. Both patients with pre-existing diabetes and new cases appear to be affected by the burn. Increased first time admissions appear only up to 5 years post-injury. Evidence for sustained disruption to glucose metabolism in burn patients. Abstract: Background: Currently, limited long-term data on hyperglycaemia and insulin sensitivity in burn patients are available and the data that do exist are primarily related to paediatric severe burns. The aim of this study was to assess if burn is associated with increased post-burn admissions for diabetes mellitus. Methods: A population-based longitudinal study using linked hospital morbidity and death data from Western Australia was undertaken of all persons hospitalized for a first burn ( n = 30, 997) in 1980–2012 and a frequency matched non-injury comparison cohort, randomly selected from Western Australia's birth registrations and electoral roll ( n = 123, 399). Crude admission rates and summed length of stay for diabetes mellitus were calculated. Negative binomial and Cox proportional hazards regression modelling were used to generate incidence rate ratios (IRR) and hazard ratios (HR), respectively. Results: After adjustment for socio-demographic factors and pre-existing health status, the burn cohort had 2.21 times (95% Confidence Interval (CI): 1.36–1.56) as many admissions and almost three times the number of days in hospital with a diabetes mellitus diagnosis (IRR, 95% CI: 2.94, 2.12–4.09) than the uninjured cohort. Admission rates were significantly elevated for those burned during childhood (<18 years, IRR, 95% CI: 2.65, 1.41–4.97) and adulthood (≥18 years, IRR, 95% CI: 2.12, 1.76–2.55). Incident admissions were significantly elevated in the burn cohort during the first 5 years post-burn when compared with the uninjured (HR, 95% CI: 1.96, 1.46–2.64); no significant difference was found beyond 5 years post-burn (HR, 95% CI: 1.08, 0.82–1.41). Conclusions: Findings of increased hospital admission rates and prolonged length of hospital stay for diabetes mellitus in the burn cohort provide evidence that burns have longer term effects on blood glucose and insulin regulation after wound healing. The first five years after burn discharge appears to be a critical period with significantly elevated incident admissions for diabetes mellitus during this time. Results would suggest prolonged clinical management after discharge and or wound healing to minimise post-burn admissions for diabetes mellitus is required.